STRATEGI FUNDRAISING BERBASIS MEDIA SOSIAL DALAM PENGHIMPUNAN DANA ZAKAT, INFAK DAN SEDEKAH DI BADAN AMIL ZAKAT NASIONAL KABUPATEN OGAN ILIR - Meirina Alkhoiriah Eka Putri; Nia Andria Erzah (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
The social media used Baznas Ogan Ilir are Instagram, whatsapp, facebook and twiter but in its implementation it is still not optimal, such as maintenance is still lacking and the use of features on each social media is still lacking so that the number of donors does not increase and tends to decrease while we are in an era where social media can be maximized for various purposes such as marketing and fundraising. This study uses a descriptive type of qualitative approach. The method used in collecting data is interviews, documentation and observation. The results of this study can be concluded that the social media based fundraising strategy is carried out in the form of collecting zakat funds, infaq, alms, fundraising and reporting in the form of flyers that will be posted Baznas Ogan Ilir social media. Then an evaluation is carried out that the fundraising carried out Baznas Ogan Ilir is in accordance with the purpose of fundraising, namely to collect. Fundraising using social media is effective because it is able to raise funds to achieve institutional targets and almost every year there is an increase in the collection of zakat, infaq and alms funds